CFD modelling of the ammonia vapour absorption in a tubular bubble absorber with NH3/LiNO3 (2021)
The absorber is a key component of absorption cooling systems, and its further development is essential to reduce the size and costs and facilitate the diffusion of absorption cooling systems. Computational fluid dynamics (CFD) can facilitate the characterization of the equipment used in absorption cooling systems at lower costs and complexity, but they must be properly developed and validated to provide reliability. This study provides a detailed description and assessment of a 3D CFD bubble absorber model developed to simulate the absorption process in a vertical double pipe with the NH3/LiNO3 solution. It includes a comprehensive methodology to develop the CFD model and its validation considering the effect of the solution flow and the cooling water temperature on absorber performance parameters such as the absorption mass flux and the solution heat transfer coefficient. The results show that the ‘Volume of Fluid model’ and the ‘Realizable k-epsilon model’ provide the lowest residuals and computational times in the simulations while a good correspondence between the CFD model and the experimental data with errors below 10% and 7% for the absorption mass flux and solution heat transfer coefficient, respectively, was obtained. The maximum absorption rate and heat transfer coefficient were 0.00441 kg m−2 s−1 and 786 W m−2 K−1, respectively.